2000
DOI: 10.1161/01.hyp.35.6.1253
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Carbon Monoxide on Baroreflex Activation in Nucleus Tractus Solitarii of Rats

Abstract: Abstract-Recent studies suggest that carbon monoxide (CO), which is produced in significant quantities in many brain regions, may function as a neurotransmitter. Heme oxygenase catalyzes the metabolism of heme to CO and biliverdin; however, the physiological role of CO in central cardiovascular regulation was not well understood. In the present study, we evaluated the baroreflex response of CO in the nucleus tractus solitarii (NTS) of rats. Male Sprague-Dawley rats were anesthetized with urethane, and blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 28 publications
4
34
2
Order By: Relevance
“…8 We have previously reported that unilateral microinjection of hematin, a heme molecule cleaved by HO to yield CO, into the NTS of anesthetized rat produce dose-related depressor and bradycardic effects. 9 On the other hand, systemic administration or direct microinjection into the NTS of HO inhibitor zinc deuteroporphyrin 2,4-bis glycol (ZnDPBG) attenuates the baroreceptor reflex. 8,9 Taken together, these findings suggest that CO within the NTS may play an important role in the regulation of cardiovascular function.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…8 We have previously reported that unilateral microinjection of hematin, a heme molecule cleaved by HO to yield CO, into the NTS of anesthetized rat produce dose-related depressor and bradycardic effects. 9 On the other hand, systemic administration or direct microinjection into the NTS of HO inhibitor zinc deuteroporphyrin 2,4-bis glycol (ZnDPBG) attenuates the baroreceptor reflex. 8,9 Taken together, these findings suggest that CO within the NTS may play an important role in the regulation of cardiovascular function.…”
mentioning
confidence: 99%
“…9 On the other hand, systemic administration or direct microinjection into the NTS of HO inhibitor zinc deuteroporphyrin 2,4-bis glycol (ZnDPBG) attenuates the baroreceptor reflex. 8,9 Taken together, these findings suggest that CO within the NTS may play an important role in the regulation of cardiovascular function.Adenosine has been known to be a potent vasodilator acting through purinergic receptors both on vascular smooth muscle and endothelial cells. This endogenous nucleoside has been studied for its potential role as a neuromodulator in a number of autonomic functions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were significant in that they provided the first experimental evidence that CO produced by HO may play a role in central regulation of blood pressure. Additional studies by Lo et al 38 also demonstrated that direct injection of ZnDBPG into the NTS decreased baroreflex sensitivity. It should again be noted that the use of metalloporphyrins as HO inhibitors is not without controversy.…”
Section: Co and The Brain: Co As A Modulator Of Baroreceptor Functionmentioning
confidence: 87%